PENGARUH KADMIUM TERHADAP GANGGUAN PATOLOGIK PADA HATI TIKUS PERCOBAAN - Anna Ratnaningsih (Jurnal Matematika Sains dan Teknologi, 2003)
Cadmium is a toxic heavy metal which causes of environmental pollution and toxic effect to the human and animal life. The specific objectives of the research were 1) to analyze cadmium content of rice and 2) to identify the effect of cadmium on liver function. The failure of liver’s function is indicated by accumulation of cadmium on liver, SGOT value and SGPT value in the serum of Wistar rats. Cadmium was administered by adding it in drinking water. The levels were composed based on highest level of cadmium found in rice. This study was performed by using four cadmium’s concentrations on drinking water which are 0 mg/L (control); 0,06 mg/L; 6,6 mg/L and 66 mg/L. Observation was conducted during 0 week; 2 weeks; 4 weeks; 6 weeks and 8 weeks. The result showed that the exposure of cadmium through drinking water caused pathophysiology effect in rats such as increasing of enzymes SGPT & SGOT and accumulation of cadmium in liver. Pathological effects such as cell degeneration of liver were also observed.